Prison reform and work programs in India: a case study. (2018) - Gupta, Namita; Gupta, Rajiv Kumar
Assigning work to prison inmates in correctional institutions is considered today a key component of prison reforms. An imprisonment of an individual not only undermines the family cohesion and security, it also destroys the income prospects of his family Hence, work programs are necessary not only for keeping inmates engaged by assigning them hard labour, but also for enabling them to earn and support economically to their families while being in jail. This further facilitates their re-integration in the community on their release. In the present paper, authors have conducted a comprehensive study on the prison work program in Model Jail Burail in Union Territory Chandigarh and lessons drawn from the study may act as a stimulus for more such initiatives in Indian prisons.